Evidencing the impact of teaching-related CPD: beyond the 'Happy Sheets'. Issue 4 (2nd October 2017) - Spowart, Lucy; Winter, Jennie; Turner, Rebecca; Muneer, Reema; McKenna, Colleen; Kneale, Pauline
Abstract: In this paper we report the outcomes of a national survey of academic development staff in a range of UK HE Institutions to consider the approaches adopted to evaluate teaching-related continual professional development (CPD). Despite the increasing drive towards accountability, the majority of respondents undertook no benchmarking to establish existing knowledge, there was minimal use of existing data sets, and few evaluated provision longitudinally. We argue that in order to arrive at an evidence-informed approach, evaluation and teaching-related CPD must be clearly conceptualised, and aligned with institutional priorities. The involvement of students with staff CPD could also be usefully explored.